The asymptotic-numerical method : an efficient perturbation technique for nonlinear structural mechanics - Cochelin, Bruno; Damil, Noureddine; Potier-Ferry, Michel (European Journal of Computational Mechanics, 1994)
Perturbation techniques (asymptotic expansions) have been widely used in many engineering fields for solving nonlinear problems. However, the solution is often represented by the first few terms of a perturbation expansion, which leads to a qualitative approximation rather than a quantitative one. Our aim is to show that a perturbation technique can also lead to a powerfull numerical method for some classes of structural problems, provided that it is combined with a finite element method to account for complex geometries, and that a large number of terms of expansions are determined.